2015
DOI: 10.1080/02699931.2015.1049936
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic facial expressions are processed holistically, but not more holistically than static facial expressions

Abstract: R. (2016). Dynamic facial expressions are processed holistically, but not more holistically than static facial expressions. Cognition and Emotion, 30 (6), 1208-1221. Dynamic facial expressions are processed holistically, but not more holistically than static facial expressions AbstractThere is evidence that facial expressions are perceived holistically and featurally. The composite task is a direct measure of holistic processing (although the absence of a composite effect implies the use of other types of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 29 publications
(54 reference statements)
0
28
0
1
Order By: Relevance
“…We used images rather than videos so that stimuli could be presented for a short duration (200 ms rather than 2 s), in order to be consistent with the prior literature on the composite effect, to limit participants' opportunity to saccade, and to increase the difficulty of the behavioral task to avoid a ceiling effect. Prior research has found comparable composite effects for dynamic stimuli (videos of expression formation) and static images of the expression formed (Tobin, Favelle, & Palermo, ). In the “aligned” condition, the top and bottom portions of the face (containing the eye/eyebrow and mouth, respectively) were presented in vertical alignment.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…We used images rather than videos so that stimuli could be presented for a short duration (200 ms rather than 2 s), in order to be consistent with the prior literature on the composite effect, to limit participants' opportunity to saccade, and to increase the difficulty of the behavioral task to avoid a ceiling effect. Prior research has found comparable composite effects for dynamic stimuli (videos of expression formation) and static images of the expression formed (Tobin, Favelle, & Palermo, ). In the “aligned” condition, the top and bottom portions of the face (containing the eye/eyebrow and mouth, respectively) were presented in vertical alignment.…”
Section: Methodsmentioning
confidence: 89%
“…The stimulus set consisted of four eye/eyebrow movements, four mouth movements, and sixteen combined (eye and mouth) movements a ceiling effect. Prior research has found comparable composite effects for dynamic stimuli (videos of expression formation) and static images of the expression formed (Tobin, Favelle, & Palermo, 2016). In the "aligned" condition, the top and bottom portions of the face (containing the eye/eyebrow and mouth, respectively) were presented in vertical alignment.…”
Section: Behavioral Paradigmmentioning
confidence: 93%
“…Moreover, our results on emotional BM are consistent with previous evidence on static vs dynamic facial expressions. In TD population the motion information seems to facilitate the recognition of facial expressions (Tobin, Favelle, & Palermo, 2016), while previous behavioural and eye tracking studies found atypical responses to facial expressions elicited by dynamic compared to static stimuli in individuals with ASD (Tardif et al 2007;Uono et al 2009). Furthermore, reduced facial mimicry in high-functioning ASD was found in responses to dynamic but not to static facial expressions and this reduction was related to social dysfunction (Yoshimura et al 2015).…”
Section: Differences Between Dynamic and Static Bm Stimulimentioning
confidence: 90%
“…Emotions were judged by decoders from dynamic video stimuli, as they more closely resemble real-life expressions (Arsalidou et al 2011), thereby offering better ecological validity (Krumhuber et al 2013). Videos are also beneficial to discriminating expression authenticity (Zloteanu et al 2018), allowing for more subtle elements of an expression to be incorporated into the decoding process (e.g., timing, duration, fluidity; Tobin et al 2016).…”
Section: The Present Studymentioning
confidence: 99%